Passive soil depressurization in Canadian homes for radon control. (15th January 2021) - Zhou, Liang (Grace); Berquist, Justin; Li, Yunyi (Ethan); Whyte, Jeffrey; Gaskin, Janet; Vuotari, Mark; Nong, Gang
Abstract: Health Canada's cross-Canada residential radon survey from 2012 demonstrated roughly 7% of Canadian homes contain radon levels above the national guideline of 200 Bq/m 3 . British Columbia (BC) is the first province in Canada to mandate a full stack passive soil depressurization (PSD) system installed within homes in radon prone areas. All other provinces within Canada require a sealed and capped rough-in pipe. In this study, PSD systems were installed in fifteen new construction homes and retrofitted in six existing homes across three provinces in Canada. This study demonstrated the potential of well-designed PSD systems to reduce radon exposure in Canadian homes, reducing indoor radon concentration below 200 Bq/m 3 in all 21 homes during multiple 30-day periods. During the winter, the PSD system was less effective in several new construction homes, whereas it appeared to operate more consistently in retrofitted existing homes. Further investigation revealed homes with a heat recovery ventilator (HRV), a ground floor bathroom, or no stack insulation were susceptible to degradation in the PSD system performance from the shoulder to winter season. Such performance degradation might be attributed to 1) HRV defrost mode causing a reduction in the ventilation air supply, 2) unsealed ground floor cut outs for the bathroom increasing the building stack effect and inducing more radon ingress through the floor slab during the winter, and 3) stacks without insulation causing frost and restricting the airflow within the stack. Graphical abstract: Image 1 Highlights: Evaluated performance of passive sub-slab depressurization in 21 Canadians homes. Effectively reduced the radon concentration to below 200 Bq/m 3 in all homes. Performance during the winter is impacted by building and system design.